From Difficulty to Understanding: Implementation of the Al-Miftah Lil Ulum Method in Reading Classical Islamic Texts (Kitab Kuning) - Mualim Wijaya; Qurrotu Aini (Universitas Al-Amien Prenduan, 2026)
Learning Arabic in Islamic boarding schools (pesantren) is fundamental to mastering classical Islamic literature (kitab kuning). However, many students face significant hurdles in grasping the complex grammatical rules of nahwu (syntax) and sharaf (morphology), leading to stagnation and decreased motivation. This study aims to analyze the implementation of the Al-Miftah Lil Ulum method in enhancing students' ability to read unvocalized Arabic texts at the Nurul Chotib Jombang Islamic Boarding School, Jember. Utilizing a qualitative approach with a descriptive case study design, data were collected through observation, interviews, and documentation. Participants were selected using purposive sampling, and the data were analyzed thematically through reduction, display, and conclusion drawing. The findings demonstrate that the Al-Miftah Lil Ulum method is effective in improving students' proficiency by utilizing a systematic, scaffolding-based approach that integrates theory and direct practice. Beyond cognitive gains, the method significantly boosts students' learning motivation and self-confidence. Nevertheless, the study identifies that teacher competence, consistency, and variations in students' initial abilities remain critical factors for success. This research concludes that the Al-Miftah Lil Ulum method serves as a strategic and applicative alternative for improving Arabic language pedagogy within the pesantren tradition. Keywords: Al-Miftah Lil Ulum, Arabic Pedagogy, Kitab Kuning, Nahwu-Sharaf, Pesantren